Riesgo cardiovascular y su relación con niveles de estrés en pacientes atendidos en el Centro de Especialidades Médicas Medser - Pucha Loarte, Mayra Daniela (2023)
Chronic psychological stress is a clear risk factor for the development of cardiovascular diseases, in the absence of local studies linking these two variables, it is considered important to assess the relationship between cardiovascular risk and stress levels in patients attending the internal medicine service of the Medser Centre for Medical Specialties, during the period from March to April 2022. This study was a quantitative approach and descriptive design with prospective and transversal vision with a sample of 110 patients, who were between 40 and 74 years old, cholesterol values determined by laboratory and had no cardiovascular disease diagnosed. The instrument for the evaluation of cardiovascular risk was the cardiovascular risk calculator of the Pan American Health Organization / World Health Organization (PAHO/WHO) and for the evaluation of psychological stress was the perceived stress scale EEP-10. The data were analyzed using the SPSS statistical program. The results determined that 34.5% of the population studied had low cardiovascular risk, 35.5% moderate risk, 25.5% high risk and 4.5% very high risk. The cardiovascular risk factors with the highest prevalence were: diabetes, hypercholesterolemia, systolic hypertension. The level of psychological stress was low at 46.4%, average at 30.9% and high at 12.7% of participants. A moderate correlation between cardiovascular risk and psychological stress was determined (r= 0.503; p<0.01).